Under Pressure: Comparison of Aspiration Techniques for Endovascular Mechanical Thrombectomy - Nikoubashman, O.; Wischer, D.; Hennemann, H.M.; Büsen, M.; Brockmann, C.; Wiesmann, M. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Blood flow should be interrupted during mechanical thrombectomy to prevent embolization of clot fragments. The purpose of our study was to provide a handy overview of the most common aspiration devices and to quantify their flow characteristics.MATERIALS AND METHODS: We assessed volumetric flow rates generated by a 60-mL VacLok vacuum pressure syringe, a Pump MAX aspiration pump, and a Dominant Flex suction pump connected to the following: 1) an 8F long sheath, 2) an 8F balloon-guide catheter, 3) an ACE 64 distal aspiration catheter, and 4) an AXS Catalyst 6 Distal Access Catheter. We used a water/glycerol solution, which was kept at a constant temperature of 20°C (viscosity, 3.7 mPa · s).RESULTS: Aspiration with the syringe and the Dominant Flex suction pump achieved the highest flows, whereas aspiration with the Pump MAX was significantly lower (P < .001). Resistors in the aspiration system (tubing, connectors, and so forth) restricted flows, especially when the resistance of the catheter was small (due to its large diameter) and the connected resistors became the predominant resistance (P < .001). The syringe achieved an average vacuum pressure of −90 kPa, and the resulting flow was constant during almost the entire procedure of filling the syringe.CONCLUSIONS: Sixty-milliliter VacLok vacuum pressure syringes and the Dominant Flex suction pump achieved high and constant flows likely sufficient to reverse blood flow during thrombectomy with an 8F sheath or balloon-guide catheter in the ICA and modern distal aspiration catheters in the MCA. The Pump MAX aspiration pump is dedicated for use with distal aspiration catheters and is unlikely to reverse blood flow in the ICA and MCA without balloon protection.